In limine Between Earth and Architecture - PIREDDU, ALBERTO (Studi e saggi, 2017)
Architecture has always been suspended in the indefinable (although necessary) tension between a 'truth to be revealed' and a 'truth to be built' and the foundation of the project is to be found, as Kenneth Frampton teaches, in the mutual relationship identified as between the topos, the typos and the 'tectonic', which is thus doubly linked to the specific conditions of a place and to the universal existence of architecture. This volume collects a set of works as found in their relationship with the Earth and that participate in the quest for the double truth mentioned above. From Verona to Fisterra and Cádiz, from Istanbul to Pompeii, the extraordinary nature of the site establishes the settlement principle, but more than that: the project, moving within the precise limits of the discipline, defines for them solid conceptual, as well as physical, bases.